Wspieranie dziecka i rodziny w edukacji szkolnej okresu transformacji = Supporting the child and family in the transformation of school education - Laska, Eugenia Iwona (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The issue of cooperation between school and family continues to be an investigated and analysed problem, which is thought to be the key to the successful upbringing. The article demonstrates the importance of teacher support along with the support from local, NGOs and government organizations. Support provided appropriately to the needs of a student and family may be an important source of inspiration to cope with many difficult situations.
Keywords: transformacja ustrojowa; szkolnictwo; dziecko; rodzina; wsparcie